Characterization of normal law by a property of the non-central χ²-distribution - Kagan, A.; Shalaevsky, O. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. М. Каган, О. В. Шалаевский. Характеризация нормального закона свойством нецентрального хи-квадрат распределения A. Kaganas, O. Šalajevskis. Normalinio dėsnio charakterizavimas necentrinio χ²-pasiskirstymo savybės pagalba